Improving "color rendering" of LED lighting for the growth of lettuce; Scientific Reports; Vol. 7 - Khan (Han) Tao; Vaganov V. A. Vitalii Andreevich; Cao Shixiu; Li Qiang; Ling Lili; Cheng Xiaoyao; Peng L. Lingling; Zhang C. Congzhi; Yakovlev A. N. Aleksey Nikolaevich; Zhong Yang; Tu Mingjing (2017, 2017)
Title screen